Advanced Access 2007 - Miles, Timothy J.; Safari eBooks ([S.l.] : CompuWorks, 2012)
"This course builds on the Introduction and Intermediate courses to show you how to bring all of the different Access objects and development phases together to make a cohesive application. It also teaches you many different techniques to make Access even more interactive by using dialog boxes, subforms, and more controls. Finally, the course shows you how to create different types of macros and how to select the proper Control and Event for the best possible outcome. The course will cover programming tips as well."--Resource description page.
Title on title screen.
Publication information from resource description page (viewed Apr. 9, 2013).
Presenter, Timothy J. Miles.
Keywords: Database management; Microsoft Access; Electronic books